KNOWLEDGE, PRACTICE AND BARRIERS OF DIABETIC FOOT SELFCARE AMONG INDIVIDUALS WITH TYPE 2 DIABETES MELLITUS - Carvalho Neto, Francisco João de; da Silva, Antônia Fabiana Rodrigues; Guimarães, Mayla Rosa; Lima, Emanuel Wellington Costa; Lima, Rafaela Pereira; Silva, Ana Roberta Vilarouca da (Cogitare Enfermagem, 2022)
Objective: To relate knowledge, practice and barriers of diabetic foot self-care among people with Type 2 Diabetes Mellitus, according to gender and education. Method: Analytical cross-sectional study with 102 users of 4 basic units in the inland of the state of Piauí, Brazil. Socioeconomic and clinical data were collected between December 2018 and July 2019. Descriptive analysis was performed with the use of the Chi-square test. Results: Women showed greater knowledge and practice of moisturizing (p<0.001), drying between the toes after bathing (p=0.020), foot hydration with moisturizing creams/oils on the heels (p<0.001), hydration on the sole of the foot (p=0.003) and use of soft and closedtoed shoes (p=0.001); there was frequent use of socks by men (p<0.001) and they were mostly made of cotton (p<0.001). There was an association between educational level and the use of shoes with heels >5cm (p=0.001) and <5cm (p<0.001). Conclusion: It is hoped that this study will allow a new type of approach aimed to the improvement of diabetic foot self-care.